Household Food Industry Hygiene and Sanitation In The Work Area Of Padang Serai Public health center In 2021 - Andriana Marwanto; Mualim Mualim; Jubaidi Jubaidi (LPPM STIKES BHAKTI HUSADA BENGKULU, 2021)
Background: Food that is safe for consumption is food that is not contaminated, does not contain microorganisms or bacteria and harmful chemicals, has been processed in the right way so that its properties and nutrients are not damaged and do not conflict with human health. In the survey conducted, there were several home industries in the Padang Serai Health Center Work Area that did not pay attention to the cleanliness of the environment around the Household Food Industry (IPRT) area so that it has the potential to cause food pollution. This study aims to determine the description of the household food industry sanitation hygiene in the working area of the Padang Serai Public Health Center in 2021 Methods: This type of research is a qualitative descriptive with an observational approach which will be carried out in March - June 2021. The subjects in this study amounted to 9 IPRTs in the Padang Serai Health Center Work area. The IPRT hygiene and sanitation data was obtained using the IPRT inspection form through interviews with the IPRT person in charge and direct observation of the IPRT condition. Results: The results showed that from 9 household food industries on the variable sanitation of buildings and production equipment 5 IPRT 55.60% was in the poor category and 4 IPRT was in good category (44.40%); variable category Hygiene facilities and activities 6 IPRT (66.70%) in poor category and good category by 3 IPRT (33.30%); Variable Health and Hygiene of employees 4 IPRT (55.60%) in poor category and good category as many as 4 IPRT (44.40%). Conclusion: the sanitation hygiene of IPRT on the variable Sanitation of buildings and production equipment is mostly 55.60% in the poor category; on the variable category of Facilities and Hygiene activities mostly 66.70% categorized as unfavorable and the variable Health and Hygiene of large employees 55.60% categorized as not good